Conducted Emission Suppression Using an EMI Filter for Grid-Tied Three-Phase/Level T-Type Solar Inverter - Halime Hizarci (IEEE Access, 2021)
Electromagnetic interference in power converters is a crucial problem for circuit designers. Electromagnetically compliant converter design is required for the safety of an operation. A novel filter design approach considering ground leakage current, different winding styles for common mode choke, tolerance of filter capacitor is proposed in this study to solve the electromagnetic interference problem. In the study, electromagnetic compatibility issue is investigated for a 25 kW, 15 kHz switching frequency, three-phase/level T-type grid-connected solar inverter. The test setup is installed based on EN55011 standard, and the interferences emitted by the inverter to the grid through conduction are measured. Then, a filter design is made to prevent these interferences from being transmitted to the grid. After the filter is designed and engaged, the measurements are repeated. So, the noise attenuation of the EMI filter is verified experimentally. Experiences obtained from the hardware modification in the EMI filter, which is designed for an industrial solar inverter, have been discussed. It is observed that the result of conducted emission measurement is within the limits of the EN55011 Class B standard.